Analysis of the Effectiveness of the Implementation of Home Affairs Ministerial Regulation No. 1 of 2016 in Resolving Legal Cases Regarding Lost Village Assets - Rifa Herawati; Yandi; Enny Agustina (Dinasti Research, 2026)
An essential part of having responsible, open, and service-oriented village leadership is managing the community's assets. Village assets are valuable for more than only their monetary and administrative worth; they are also a strategic tool for the development and well-being of village communities. However, there are still many issues in reality, and one of them is the possible loss of local assets due to poor governance. This might lead to financial hardship for the village. There has been little research on the efficacy of Minister of Home Affairs Regulation Number 1 of 2016 in addressing instances of missing village assets, however it does provide a legal framework for village asset management. The purpose of this research is to examine the Minister of Home Affairs Regulation No. 1 of 2016 and its impact on village governance practices, specifically looking at the legal settlement procedure for lost village assets. Legislative, conceptual, and case-based empirical research methodologies are used in this study. examination of relevant literature, research of applicable regulations, and examination of relevant village asset management methods were used to collect the data. Asset identification, administrative examination, responsibility determination, administrative sanctions, or further legal steps if civil or criminal elements are found are the stages that make up the legal resolution mechanism for the loss of village assets, according to the research results. Normative shortcomings in technical rules, inadequate ability of village officials, insufficient supervision mechanisms, and an absence of a robust administrative legal culture at the village level have all contributed to the ineffective implementation of Home Affairs Ministerial Regulation Number 1 of 2016. Therefore, it is necessary to strengthen technical regulations, increase the capacity of village government officials, and optimize participatory oversight to realize more effective, accountable, and sustainable village asset governance.